Chronic Obstructive Pulmonary Disease Individualized Therapy: Tailored Approach to Symptom Management - Singh, Dave (Adv Ther, 2016)
Chronic obstructive pulmonary disease (COPD) is associated with high morbidity and mortality. COPD is typified by persistent, progressive airflow limitation and a range of respiratory and systemic symptoms such as breathlessness, coughing, wheezing, depression, anxiety, general fatigue, and sleeping difficulties. Despite receiving treatment for COPD, many patients suffer from regular symptoms that affect their daily lives and lead to increased morbidity. These symptoms vary in severity, frequency, and type, and can occur at any time throughout the 24-h day, with over half of patients with COPD experiencing symptoms in the morning, during the day, and at nighttime. Despite the prevalence of symptoms, patient and physician perception of the impact of COPD symptoms on patients’ lives is not always in concordance. Dual bronchodilator therapy with a long-acting muscarinic antagonist (LAMA) and long-acting beta agonist (LABA) has the potential to treat the symptoms of COPD in addition to improving lung function. This review therefore examines the burden of symptoms experienced throughout the day by patients with COPD and the evidence for combined LAMA/LABA treatment in terms of symptom management. As patients with COPD experience varying symptoms throughout the course of their disease, the role of tailoring treatment to the individual needs of the patient is also examined. We conclude that the symptoms of COPD are troublesome, variable, can occur during all parts of the 24-h day, and have a substantial impact on patients’ health status and quality of life. In order to provide effective, patient-orientated care, patients with COPD should be evaluated on the basis of lung function, the frequency of symptoms, and patient-perceived impact of symptoms on their lives. Therapy should be chosen carefully based on individualized assessment, ensuring personalization to the individual needs of the patient.